Comparative Analysis of Gene Expression Data Reveals Novel Targets of Senescence-Associated microRNAs - Napolitano, Marco (Public Library of Science, 2014)
In the last decades, cellular senescence is viewed as a complex mechanism involved in different processes, ranging from tumor suppression to induction of age-related degenerative alterations. Senescence-inducing stimuli are myriad and, recently, we and others have demonstrated the role exerted by microRNAs in the induction and maintenance of senescence, by the identification of a subset of Senescence-Associated microRNAs (SAmiRs) up-regulated during replicative or stress-induced senescence and able to induce a premature senescent phenotype when over-expressed in human primary cells. With the intent to find novel direct targets of two specific SAmiRs, SAmiR-494 and -486-5p, and cellular pathways which they are involved in, we performed a comparative analysis of gene expression profiles available in literature to select genes down-regulated upon replicative senescence of human primary fibroblasts. Among them, we searched for SAmiR’s candidate targets by analyzing with different target prediction algorithms their 3’UTR for the presence of SAmiR-binding sites. The expression profiles of selected candidates have been validated on replicative and stress-induced senescence and the targeting of the 3’UTRs was assessed by luciferase assay. Results allowed us to identify Cell Division Cycle Associated 2 (CDCA2) and Inhibitor of DNA binding/differentiation type 4 (ID4) as novel targets of SAmiR-494 and SAmiR-486-5p, respectively. Furthermore, we demonstrated that the over-expression of CDCA2 in human primary fibroblasts was able to partially counteract etoposide-induced senescence by mitigating the activation of DNA Damage Response.